Psychosocial distress and associated factors among adult cancer patients at oncology: a case of Ethiopia - Baye, Astewle Andargie; Bogale, Sitotaw Kerie; Delie, Abebu Tegenaw; Melak Fekadie, Mengistu; Wondyifraw, Haileyesus Gedamu; Tigabu, Mengistu Ewunetu; Kebede, Mulu (Frontiers in Oncology, 2023)
Background Psychosocial distress is a chronic burden for cancer survivors, which impacts both their quality of life and their oncologic prognosis. Although the national cancer prevention and control program in Ethiopia has made efforts in cancer prevention, control, and management by implementing the national cancer control plan 2016–2020, there was no enough evidence about psychosocial distress among adult cancer patients. So, it is critical to understand the magnitude of psychosocial distress and the factors that contribute to it. Objective The purpose of this study was to assess the prevalence of psychosocial distress and associated factors among adult cancer patients at oncology units in the Amhara regional state, Ethiopia. 2022. Methods A multicenter institution-based cross-sectional study was conducted among a sample of 605 adult cancer patients from 30 April to 22 June 2022. A systematic random sampling technique was employed to select the study units. In addition, data were collected through interviewers administered questionnaires by using the validated and pretested tools. Distress was assessed using the Questionnaire on Stress in Cancer Patients Revised 10. Both bivariable and multivariable logistic regression was used to describe the association between dependent and independent variables. Independent variable with p < 0.25 in the bivariable logistic regression analyses were entered into multivariable logistic regression model. Variables with p < 0.05 in the multivariable logistic regression analyses were considered as statistically significant associated factors of psychosocial distress. Result A total of 593 adult cancer patients took part in this study with mean age of 46.86 ± 14.5 years. The overall prevalence of psychosocial distress was 63.74%. Variables such as being female [AOR = 1.98, 95% confidence interval (CI): 1.24–3.17], patients who lives in rural areas (AOR = 2.3, 95% CI: 1.49–3.54), community-based health insurance utilization (AOR = 0.34, 95% CI: 0.23–0.51), patients on chemotherapy treatment (AOR = 2.72, 95% CI: 1.38–5.39), patients with comorbidity (AOR = 3.2, 95% CI: 1.67–6.10), and symptom burdens such as severe fatigue (AOR = 1.65, 95% CI:1.09–2.39) and severe nausea (AOR = 2.07, 95% CI: 1.43–3.00) were statistically associated with psychosocial distress. Conclusion and recommendation In general, the findings of this study showed a relatively high magnitude in which around two-thirds of patients experienced psychosocial distress. It is better to establish and enforce the integration and coordination of psychosocial oncology service programs at national level with parallel guidelines and policies.